Surgical treatment and outcomes in feline aortic thromboembolism: a retrospective study of 13 cats - Li, Jin; Zhou, Yuhu; Liu, Yanhai; Ma, Qingbo; Peng, Jingwen; Li, Meng (Frontiers in Veterinary Science, 2025)
ObjectivesThis study aimed to evaluate the survival and survivor characteristics in cats diagnosed with feline aortic thromboembolism (FATE) who underwent surgical aortic thrombectomy.MethodsMedical records from 2021 to 2023 were retrospectively reviewed for cats diagnosed with FATE that underwent surgical aortic thrombectomy. Data collected included signalment, medical history, clinical examination findings, laboratory parameters before and after surgery, the time from FATE onset to surgery, treatments administered, survival to discharge, and recurrence or long-term outcomes in discharged cats.ResultsThirteen client-owned cats met the inclusion criteria. Common postoperative laboratory abnormalities observed during hospitalization included azotemia (n = 8), anemia (n = 4), hyperkalemia (n = 4), and elevated alanine aminotransferase (n = 3). After surgery, 53.8% of the cats survived to discharge, with 71.4% showing complete recovery of hind limb motor function. Among the discharged cats, two (28.6%) were confirmed deceased during follow-up, while five (71.4%) were lost to follow-up. The median follow-up duration was 37 days (14–498). Recurrence of FATE occurred in two cats (28.6%) at 77 and 493 days postoperatively; both were successfully managed with medical treatment and survived to discharge again. Cats that survived had significantly lower preoperative neutrophil-to-lymphocyte ratios (p = 0.033), postoperative serum potassium levels (p = 0.037), and postoperative blood urea nitrogen concentrations (p = 0.037) than non-survivors.Conclusion and relevanceCats undergoing surgical aortic thrombectomy for FATE showed a 53.8% survival rate to discharge, with 71.4% of survivors achieving full recovery of limb motor function. Surgical aortic thrombectomy may be considered as a treatment option for cats with FATE, particularly when timely presentation allows for early intervention.